Implementation of A* Algorithm and Contraction Hierarchies for Delivery Route Optimization (Case Study: CV. Almaed.id) - Gunawan, Boy Erdyansyah; Idhom, Mohammad; Akbar , Fawwaz Ali; Riyantoko, Prismahardi Aji (International Journal of Computer, Network Security and Information System, 2024)
In the digital era, manufacturing companies like CV. Almaed.id are required to have an efficient distribution system to compete in the furniture industry. This study proposes the application of the A* algorithm and Contraction Hierarchies (CH) to optimize product delivery routes. This system utilizes road network data from OpenStreetMap and calculates geographic distances using the Haversine method. Implementation results show that the combination of A*, CH, and Haversine can accelerate route calculation and reduce operational costs compared to manual methods.